Human Cardiac Progenitor Cells Enhance Exosome Release and Promote Angiogenesis Under Physoxia - Dougherty, Julie A.; Patel, Nil; Kumar, Naresh; Rao, Shubha Gururaja; Angelos, Mark G.; Singh, Harpreet; Cai, Chuanxi; Khan, Mahmood (Frontiers in Cell and Developmental Biology, 2020)
Studies on cardiac progenitor cells (CPCs) and their derived exosomes therapeutic potential have demonstrated only modest improvements in cardiac function. Therefore, there is an unmet need to improve the therapeutic efficacy of CPCs and their exosomes to attain clinically relevant improvement in cardiac function. The hypothesis of this project is to assess the therapeutic potential of exosomes derived from human CPCs (hCPCs) cultured under normoxia (21% O2), physoxia (5% O2) and hypoxia (1% O2) conditions. hCPCs were characterized by immunostaining of CPC-specific markers (Nkx2.5, GATA4, and c-kit). Cell proliferation and cell death assay was not altered under physoxia. A gene expression qPCR array (84 genes) was performed to assess the modulation of hypoxic genes under three different oxygen conditions as mentioned above. Our results demonstrated that very few hypoxia-related genes were modulated under physoxia (5 genes upregulated, 4 genes down regulated). However, several genes were modulated under hypoxia (23 genes upregulated, 9 genes downregulated). Furthermore, nanoparticle tracking analysis (NTA) of the exosomes isolated from hCPCs under physoxia had a 1.6-fold increase in exosome yield when compared to normoxia and hypoxia conditions. Furthermore, tube formation assay for angiogenesis indicated that exosomes derived from hCPCs cultured under physoxia significantly increased tube formation as compared to no-exosome control, 21% O2, and 1% O2 groups. Overall, our study demonstrated the therapeutic potential of physoxic oxygen microenvironment cultured hCPCs and their derived exosomes for myocardial repair.